Case Report: Assessing the Position of Pacemaker Leads via Transthoracic Echocardiography: Additional Value of the Subcostal En Face View - Deichl, Andrea Simone; Lacour, Philipp; Belyavskiy, Evgeny; Pieske, Burkert; Pieske-Kraigher, Elisabeth; Blaschke, Florian; Schneider, Matthias (Frontiers in Cardiovascular Medicine, 2021)
There is an association between presence of cardiac implantable electronic devices (CIED) and development of tricuspid regurgitation (TR). Mechanisms proposed to explain CIED-induced TR can be classified as implantation-related, lead-related, and pacing-related. Lead-related TR results from the direct interaction of the lead with the tricuspid valve (TV). The localization of the lead at the TV level directly influences the probability of subsequent development of significant TR. A transthoracic subcostal en face view of the TV can be acquired in most patients through a 90° rotation from the subcostal 4-chamber view with clear anatomic delineation of the TV and the commissures including lead position. This case-series presents three examples where the transthoracic en face view could add incremental information on the position of the pacemaker leads and on the mechanism of TR. Conclusion: When performing transthoracic echocardiography in patients with trans-tricuspid CIED lead(s), an en face view of the TV with exact reporting of the position of the lead(s) should be included.